STRATEGIC USE OF EROTIC CAPITAL IN CHALLENGING PATRIARCHY: THE CASE OF KURIYEDATH THATRI AND ITS CINEMATIC REPRESENTATION IN PARINAYAM - Rajagopalan, Vaidehi; Dr. Ann Mary George (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The article examines the concept of erotic capital and its use by women to fight against the patriarchal system, with a focus on the historical figure, Kuriyedath Thatri (also called Thatrikutty) from the Namboodiri community in Kerala. The study aims to understand Thatrikutty’s strategic deployment of erotic capital, which marked an end to the chastity trial of smarthavicharam within the community. Additionally, it critiques the 1994 Malayalam movie Parinayam, which is based on Thatrikutty’s life, for its lack of portrayal of erotic capital. Employing a qualitative analysis, the study begins with an overview of the condition of Namboodiri women and the concept of smarthavicharam. It then delves into how Thatrikutty used her erotic capital as a weapon against the oppressive system. Subsequently, the article shifts focus to the movie Parinayam, detailing the film’s failure to depict erotic capital. The findings reveal how women can use erotic capital as a powerful weapon to challenge patriarchal oppressions, as exemplified by Thatrikutty’s actions. The study also finds out that the lack of portrayal of erotic capital in the movie Parinayam, accounts to the attempt to suit the movie to societal thoughts, concerning the response of a wide audience.